THERMODYNAMIC PROPERTIES OF ALMANDINE-GROSSULAR GARNET SOLID-SOLUTIONS - Cressey, G; Schmid, R; Wood, B (Springer-Verlag, 1978)
The mixing properties of Fe3Al2Si3O12-Ca3Al2Si3O12 garnet solid solutions have been studied in the temperature range 850-1100° C. The experimental method involves measuring the composition of garnet in equilibrium with an assemblage in which the activity of the Ca3Al2Si3O12 component is fixed. Experiments on the assemblage garnet solid solution, anorthite, Al2SiO5 polymorph and quartz at known pressure and temperature fix the activity of the Ca3Al2Si3O12 component through the equilibrium: Mathematical expression This equilibrium, with either sillimanite or kyanite as the aluminosilicate mineral, was used to control Mathematical expression. The compositions of the garnet solutions produced were determined by measurement of their unit cell edges. At 1 bar Fe3Al2Si3O12-Ca3Al2Si3O12 garnets exhibit negative deviations from ideality at the Fe-rich end of the series and positive deviations at the calcium end. With increasing pressure the activity coefficients for the Ca3Al2Si3O12 component increase because the partial molar volume of this component is greater than the molar volume of pure grossular. Previous studies indicate that the activity coefficients for the Ca3Al2Si3O12 component also increase with increasing (Mg/Mg+Fe) ratio of the garnet. The region of negative deviation from ideality implies a tendency towards formation of a stable Fe-Ca garnet component. Evidence in support of this conclusion has been found in a natural Fe-rich garnet which was found to contain two different garnet phases of distinctly different compositions. © 1978 Springer-Verlag.